2019
DOI: 10.1088/1755-1315/305/1/012065
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Phenol and Antioxidant Compounds from Kepok Banana Skin with PEF Pre-Treatment

Abstract: Kepok banana (Musa parasidiaca L) consumption produce banana skin waste that is only used as animal feed and house waste. Kepok banana peel contains phenol and antioxidants of 12.35% and other compounds. These compounds can be extracted using maceration methods. A pre-treatment process is needed to increase phenol compounds and antioxidants using Pulsed Electric Field (PEF). The advantage of using PEF pre-treatment is that it can break down the cell membrane with the electric shock without using high temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The authors stated that using PEF increased TPC in extracts from CBS and coffee silver skin by 1.8–19.5% and 3–21%, correspondingly, compared with CE. Comparable findings have been reported on PEF extraction of lemon peel’s polyphenols [ 161 ], tepals of Crocus sativus [ 168 ], olive pomace [ 163 ], Sideritis raiseri [ 169 ], apple pomace [ 170 ], banana peels [ 171 ] and potato peels [ 162 ].…”
Section: Non-thermal Extraction Methodsmentioning
confidence: 76%
“…The authors stated that using PEF increased TPC in extracts from CBS and coffee silver skin by 1.8–19.5% and 3–21%, correspondingly, compared with CE. Comparable findings have been reported on PEF extraction of lemon peel’s polyphenols [ 161 ], tepals of Crocus sativus [ 168 ], olive pomace [ 163 ], Sideritis raiseri [ 169 ], apple pomace [ 170 ], banana peels [ 171 ] and potato peels [ 162 ].…”
Section: Non-thermal Extraction Methodsmentioning
confidence: 76%
“…Hendrawan et al [ 54 ] demonstrated that PEF, rather than a standalone extracting method, is a useful preliminary procedure to increase the phenolic yield recovered from Kepok banana peel. In fact, both the total phenolic content and antioxidant activity were higher than in the control sample not pre-treated with PEF (1.090 ± 0.165 mg GAE/g dry extract).…”
Section: Alternative Methods For Green Extraction Of Bioactive Compou...mentioning
confidence: 99%
“…In fact, both the total phenolic content and antioxidant activity were higher than in the control sample not pre-treated with PEF (1.090 ± 0.165 mg GAE/g dry extract). In their study, the electric field strength of 4 kV/cm for 2 min led to the highest value of total phenol content (1.664 ± 0.226 mg GAE/mg dry extract), while considering antioxidant activity, the highest value was reached using the same electric field strength for 4 min (IC 50 = 13.086 ± 4.547 mg/mL; DPPH assay) [ 54 ].…”
Section: Alternative Methods For Green Extraction Of Bioactive Compou...mentioning
confidence: 99%
“…PEF has been applied mostly in the food industry for the reduction of microbial growth/pasteurization and for the enhanced extraction of phytochemicals from fruit and vegetable industry wastes [15,17,18,20,[23][24][25][26][27]. Bobinaitė et al (2015) [23] investigated the influence of PEF pretreatment on the recovery of bioactive compounds from by-products (press cake) of blueberry fruits (Vaccinium myrtillus L.).…”
Section: Of 11mentioning
confidence: 99%